015 'I actually only come to work for the banter': a qualitative study into contributors to emergency department care providers' transitory emotional state. Issue 12 (21st November 2019) - Roy, Susie; Jaap, Alan; Skinner, Janet
Abstract : Background: Our affective (emotional) state has far reaching and well recognised implications relating to well-being, team-work and patient safety. The aim of this novel study was to gain an in depth understanding of factors that influence the transitory emotions of Emergency Department (ED) care providers whilst at work. Method and results: Using a pragmatist theoretical lens, a qualitative methodology was selected to explore staff members' experiences of factors generating positive and negative emotions. Focus groups were facilitated with ED staff from a major acute teaching hospital in Scotland. Purposive sampling was used to recruit participants, with each group containing members of the same or similar grade and occupation. Consultant, higher specialty trainee, junior doctor and nursing focus groups were undertaken. Following transcription, data were coded and thematically analysed to arrive at key concepts. Conclusions: Six main themes were identified: ' ED team rapport' referring to the personalities and attitudes of those working that day; 'achievement' with successful task completion, skill use, being thanked and constructive educational opportunities generating positive emotions and lack of this feeling generating the converse; 'interpersonal interactions' where the negative impact of incivility from staff or patients was highlighted; 'equipment/infrastructure' showcasing how frustration manifests when either fails; 'the open and the close' representing the impact of how the tone set in handover influences affect and finally, the self-explanatory 'a bad day outside work can influence that inside.' This study illustrates the importance of recognising personal 'wins' whether that be a well-managed patient or successfully recognised teaching opportunity. It adds impetus to the campaign against incivility - reaffirming the negative effect rudeness has on affect. On a personal level, it highlights that we can take responsibility to 'choose our own weather' as a team member or leader in being a colleague that others enjoy working with. This may improve outcomes for all.